Geographic disparities in pancreatic cancer survival in a southeastern safety‐net academic medical center. (19th May 2015) - Markossian, Talar W.; O'Neal, Cindy‐Marie; Senkowski, Christopher
Abstract: Objective: To quantify the effects of race, measures of socioeconomic status and geographic residency status on pancreatic cancer survival time. Design: Retrospective review. Setting: A southeastern safety‐net academic medical centre in the United States. Participants: The study population consisted of all patients who were diagnosed, referred to or treated at the medical centre between 2009 and 2012 ( n  = 245). To ensure completeness and accuracy of the data, follow‐up treatment and survival information about the cases were collected from the Georgia Comprehensive Cancer Registry in 2013. Main outcome measures: The odds of receiving first‐course treatment (surgery, radiation or chemotherapy) and overall survival following a pancreatic cancer diagnosis. Results: There were no observed differences in receipt of initial treatment; however, patients from low socioeconomic and rural areas had significant increase in risk of death compared to patients from affluent and urban areas. Conclusions: Results from this single site study suggests the significance of factors other than treatment differences that contribute to geographic disparities in mortality.